Circulating BPIFB4 Levels Associate With and Influence the Abundance of Reparative Monocytes and Macrophages in Long Living Individuals - Ciaglia, Elena; Montella, Francesco; Lopardo, Valentina; Scala, Pasqualina; Ferrario, Anna; Cattaneo, Monica; Carrizzo, Albino; Malovini, Alberto; Madeddu, Paolo; Vecchione, Carmine; Puca, Annibale Alessandro (Frontiers in Immunology, 2020)
Long-Living Individuals (LLIs) delay aging and are less prone to chronic inflammatory reactions. Whether a distinct monocytes and macrophages repertoire is involved in such a characteristic remains unknown. Previous studies from our group have shown high levels of the host defense BPI Fold Containing Family B Member 4 (BPIFB4) protein in the peripheral blood of LLIs. Moreover, a polymorphic variant of the BPIFB4 gene associated with exceptional longevity (LAV-BPIFB4) confers protection from cardiovascular diseases underpinned by low-grade chronic inflammation, such as atherosclerosis. We hypothesize that BPIFB4 may influence monocytes pool and macrophages skewing, shifting the balance toward an anti-inflammatory phenotype. We profiled circulating monocytes in 52 LLIs (median-age 97) and 52 healthy volunteers (median-age 55) using flow cytometry. If the frequency of total monocyte did not change, the intermediate CD14++CD16+ monocytes counts were lower in LLIs compared to control adults. Conversely, non-classical CD14+CD16++ monocyte counts, which are M2 macrophage precursors with an immunomodulatory function, were found significantly associated with the LLIs’ state. In a differentiation assay, supplementation of the LLIs’ plasma enhanced the capacity of monocytes, either from LLIs or controls, to acquire a paracrine M2 phenotype. A neutralizing antibody against the phosphorylation site (ser 75) of BPIFB4 blunted the M2 skewing effect of the LLIs’ plasma. These data indicate that LLIs carry a peculiar anti-inflammatory myeloid profile, which is associated with and possibly sustained by high circulating levels of BPIFB4. Supplementation of recombinant BPIFB4 may represent a novel means to attenuate inflammation-related conditions typical of unhealthy aging.